Volland, Wabaunsee County - Laidacker, Emmalee (Kansas State University, The Chapman Center for Rural Studies, 2016)
Volland was a town that almost met its end when the railroad it heavily depended on for commerce and revenue became obsolete due to new technology. Against all odds, however, the town would survive and experience a rebirth. This study incorporates information from new and old photographs, interviews, and newspaper articles.
Emmalee Laidacker, “Volland, Wabaunsee County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/162.
Keywords: Volland; Wabaunsee County; African-Americans; World War II; Civil War; German Immigrants